Magic School Ai In Designing Indonesian Language Learning For Second Grade With A Deep Learning Paradigm - Cahyani, Ayuditya Widya; Yudono, Kristophorus Divinanto Adi (Institut of Shanti Bhuana, 2025)
Magic School AI is one of the tangible manifestations of the development of digital technology that provides opportunities to improve the quality of learning. One of the features that Magic School AI has is designing learning activities. The purpose of this study is to describe the performance of the Magic School AI artificial intelligence application in designing Indonesian learning activities for second grade students. This research is qualitative research with a virtual ethnographic method. Data collection was carried out by observation and interviews. The duration of Magic School AI usage is one month. Magic School AI is used to design Indonesian learning in accordance with the latest curriculum paradigm, namely Deep Learning. The results of this research are that Magic School AI has features that can be used to produce diagnostic assessments, produce project-based lesson plans, improve the visual quality of learning, and produce learning support texts. However, teachers need to modify and review the ideas of Magic School AI to fit the latest learning paradigms, conditions, and learning needs experienced by the learning environment.